2008
DOI: 10.1111/j.1442-2050.2000.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir and globe-type antireflux surgical techniques in intrathoracic esophagogastrostomies

Abstract: Gastroesophageal re¯ux is a major postoperative problem in esophageal patients with cancer, and the principal cause is resection of the lower esophageal sphincter. Two new antire¯ux operations to solve this problem were investigated. The number of patients studied was 139, with a male to female ratio of 5. The reservoir technique was applied to the ®rst 50 patients and the globe technique was used in the remaining 89. Hospital mortality was 9.35%. Patient satisfaction from a re¯ux standpoint was excellent in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A number of surgical techniques attempting to control reflux after esophagectomy have been reported 5 including intercostal muscle grafts to act as anti-reflux valves, 21 tunneling the esophagus through the muscular layer of the stomach 22,23 "inkwelling" 24,25 or creating a "globe" posteriorly invaginated anastomosis. 26 None have been subjected to a randomized controlled study and have historically been described in the setting of limited or palliative resections offering a substantial esophageal and or gastric remnantsomething not available after modern radical resection for cancer. 27 The use of colonic interposition after esophageal resection eliminates gastro-duodenal secretions and, therefore, reflux.…”
Section: Regurgitation Severity Scorementioning
confidence: 99%
“…A number of surgical techniques attempting to control reflux after esophagectomy have been reported 5 including intercostal muscle grafts to act as anti-reflux valves, 21 tunneling the esophagus through the muscular layer of the stomach 22,23 "inkwelling" 24,25 or creating a "globe" posteriorly invaginated anastomosis. 26 None have been subjected to a randomized controlled study and have historically been described in the setting of limited or palliative resections offering a substantial esophageal and or gastric remnantsomething not available after modern radical resection for cancer. 27 The use of colonic interposition after esophageal resection eliminates gastro-duodenal secretions and, therefore, reflux.…”
Section: Regurgitation Severity Scorementioning
confidence: 99%
“…Other studies show a variation from 27 to 42% or more in the occurrence of anastomotic stenosis, esophageal-gastric patients undergoing esophagectomy 16 , showing that the incidence observed in our study is in agreement with the literature. In eletromanometric study, we observed that the average pressure of the anastomosis in the patients studied was 7.55mmHg, while Yalav and Ercan 4 showed an average pressure of 14.2mmHg in cases of intra-thoracic anastomosis with performance of antireflux valve in order to reduce aggression to the esophageal stump. In our study, although the lower average, the anastomosis is near the upper esophageal sphincter, which showed an average pressure of 24.83mmHg which seems to favor the prevention of the occurrence of gastroesophageal reflux.…”
Section: Discussionmentioning
confidence: 86%
“…The chagasic megaesophagus has as its main pathological findings a strong intramural denervation that affects the almost entirely the middle and lower esophageal There are several reports in the literature about the anatomical and functional changes of the remaining esophageal stump after subtotal esophagectomy, especially in the treatment of esophageal cancer 4 . However, for the treatment of achalasia reports are still few, which encouraged us to investigate these possible changes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The upper bar represents the incidence in patients whose corrected anastomotic height was less than 0.154 (median value); the lower bar represents the incidence in patients whose corrected anastomotic height was more than 0.154 68% of the ITA patients had to sleep in an upright position because of refl ux problems. Several anastomotic techniques have been used to construct a new antirefl ux barrier after resection of an esophagogastric junction [21][22][23][24]. The technique that we used with the ITA was similar to the reservoir technique introduced by Yalav et al [24].…”
Section: Prognosismentioning
confidence: 99%
“…Several anastomotic techniques have been used to construct a new antirefl ux barrier after resection of an esophagogastric junction [21][22][23][24]. The technique that we used with the ITA was similar to the reservoir technique introduced by Yalav et al [24]. Self-evaluations by the patients in that study on the severity of postoperative refl ux symptoms were excellent, with no symptoms of refl ux being reported by 91% of the patients who underwent the reservoir technique or another antirefl ux technique.…”
Section: Prognosismentioning
confidence: 99%